(untitled) (KIUT Publication, 2025)
The article describes the research devoted to the issues of creating a comfortable urban environment in hot climates, in particular, the implementation of solutions that reduce the impact of high temperatures and solar radiation on pedestrians. In particular, it deals with a pedestrian walkway canopy with a new type of structural solution. It emphasizes the technical and economic advantages of this new type of canopy design. Furthermore, it is explained that the canopy can serve factors such as energy efficiency.